Necesidad de implementar la caducidad de las concesiones mineras por falta de servidumbre, como garantía al derecho de la propiedad privada, en la ley de minería - González Villalta, Jeimmy Paulina (2015)
The history of the mining in Ecuador goes back B.C. to 3500 years In the period Late Valdivia, the first materials coming from excavations were used to obtain clay and mud. Later on, in the cultures Machalilla and Spout, all these arts are perfected and the extraction of materials was intensified. In the culture The Tolita and Pampas of Gold, the metallurgy is developed intensely and mainly the gold is used to elaborate diverse objects. The gold is obtained then in that of diverse sources, mainly gold of alluvial origin (How up to now it is made in some regions). In 1532 with the Spanish conquest of the Tahuantinsuyo a stage began where the extraction of the gold was intense. The century 16 are the century of the gold. It begins with the looting of the Spaniards of what the natives elaborated in gold and silver. During the time of the independence, by means of an ordinance signed by the Liberator Simón Bolívar, it was declared exempt of the military service to all the people that wanted to be devoted to the mining, to motivate this activity. In 1900, Eloy Alfaro modified the code of mining of 1886, establishing the term of the lease of the mines until for 50 years; but then, when going up the government Leonidas Square, this was modified code again, establishing the lease from the mines to perpetuity. Under this outline, in 1921, the geologist of the United States Benjamin Franklin Wallis received the license to explore mines in the Cojitambo and in Cuenca. The Colombian Cicero Castle continued him, who obtains permission to explore and to exploit mines in Nulti, Paccha and Santa Ana, in the canton Cuenca; and in Déleg and Cojitambo, in the canton Quicksilvers. Later on, to the south of the Ecuador (mainly in Zaruma and Portovelo) in 1915 the mining company South American Development, to the control of Mellick Tweedy, undertook the exploitation of gold for a 30 year-old period, taking advantage of a resource that the Ecuadorians until then they never knew how to use. The mining of gold in the south of the Ecuador has caused considerable environmental impacts, being the most severe those of the areas Portovelo-Zaruma and Ponce Enríquez. The main pollutants are cyanide, heavy metals and mercury. The most significant sources in these pollutants are the direct discharged lines or indirectly in the rivers, for the inadequate disposition systems. The discharge of these pollutants has caused the extinction in all way of superior life in certain tracts of the rivers; also, in several places, the bad quality of the water disables its use as drinkable water, for irrigation or aquatic hatcheries, the private property had been the main one affected the owner of the underground since is the State who grants the ability to l mining concessionaire so that it exploits the minerals, leaving defenseless the property of matters or fertile floor, what causes to harm of right and consequently, people owners of the adjacent properties where they are carried out the mining works they have been directly affected. April 18 the 2008, the Constituent Assembly of the Ecuador, sends the famous Mining Command, by means of which all the mining concessions that had not been legalized extinguished and they didn't have its respective Study of Environmental Impact. In the text of the Constitution of Montecristi he wears away even more that in the previous constitutions the protection of the private property. It happens that this it is the main guarantee of the individual freedoms. But our generation has forgotten this that if the production means are concentrated in a single couple of hands, either nominally in hands of the whole society or in those of a dictator who it is that it possesses this control he/she has to be able to total for on us. The current constitution recognizes seven types of private property and he/she this way what is and it is not private property. What is not clearly defined won't be easy to defend. The private property presupposes inequality of revenues, and if it is looked for to fulfill several promises of material equality, it will necessarily be necessary to tunnel the private property since the same Constitution of the Republic of the Ecuador he/she settles down, the equal redistribution of the resources and the wealth, guarantee the formal equality, material equality, that which implies to remove those that have more to give to those that he/she has in the practice less, transgressing this way the right to the private property of some for benefit of other, guarantees the equitable distribution of the benefits of the development. Not you specific but for what says in other parts the text, it is assumed that this refers to the equitable distribution of the revenues, he/she intends the redistribution of agricultural lands through the State, public politics that so many times have been rehearsed in Latin America and in our country without having generated a distribution that favors the peasants but alone to the elite that made the redistribution; the State will look after the appropriate distribution of the entrance. To weigh that the mining Law establishes that the mining concessionaires should obtain the servitude with the adjacent properties to be able to exploit the minerals of the underground, a politics of expiration doesn't settle down for servitude lack toward the mining concessionaires, and you It affects the right to the private property, taking in consideration that should be obtained the consent of the adjacent property first or of the owner of the superficial land where he/she will be carried out the mining exploitation. It is for these reasons that one needs to implement the expiration for servitude lack in the Law of Mining, and this way to protect in some way the private property when you explodes of inadequate way and technical anti and without permission, the superficial properties.